HUBUNGAN TIMBULNYA ACNE VULGARIS DENGAN TINGKAT KECEMASAN PADA REMAJA DI SMP N 1 LIKUPANG TIMUR - Sampelan, Meiching G; Pangemanan, Damayanti; Kundre, Rina (JURNAL KEPERAWATAN, 2017)
Abstract:Acne vulgaris is a condition where the clogged pores and raised red spots and abscesses (pockets of pus) to become inflamed and infected skin. Acne commonly appears on the face, neck, and back among girls aged 14-17 years, while teenage boys at the age of 16- 19 years. Acne vulgaris physical and psychological impact on juvenile form of anxiety and depression.Objective Acne Vulgaris emergence relationship with the level of anxiety in adolescents in SMP N 1 Likupang East.The study design is cross sectional and using questionnaires and observations to obtain data from respondents.Research resultThe results of a study of 42 students found 62% experiencing mild acne vulgaris, 19,0% experienced severe acne vulgaris. Most respondents experiencing mild acne vulgaris as much as 62,0%.The level of anxiety in students gained as much as 64,3% of students experiencing mild anxiety, anxiety was 19,0%, and 16,7% had severe anxiety. The majority of student anxiety is mild anxiety with the amount of 64,3%.And using Chi-Square can be p-value of 0.000 (Î± 0.05).Conclusion No significant positive correlation between the incidence of acne vulgaris relationship with the level of anxiety in Adolescents in SMP N 1 Likupang East. Keywords : Acne Vulgaris, levels of anxiety Abstrak : Acne vulgaris adalah suatu keadaan dimana pori-pori kulit tersumbat sehingga timbul bintik merah dan abses (kantong nanah) yang meradang dan terinfeksi pada kulit. Jerawat sering terjadi pada kulit wajah, leher dan punggung dan terdapat pada perempuan umur 14-17 tahun laki-laki umur 16-19 tahun. Acne vulgaris mempunyai dampak bagi Remaja secara fisik maupun psikologik dan dapat menimbulkan kecemasan dan depresi. Tujuanmengetahui hubungan timbulnya Acne Vulgaris dengan tingkat kecemasan pada remaja di SMP N 1 Likupang Timur. Desain Penelitian yaitucross sectionaldan menggunakan kuesioner serta observasi untuk mendapatkan data dari responden. Hasil Penelitian dari 42 siswa didapatkan acne vulgaris ringan 62,0%, sedang 19,0% dan berat 19,0%. Sebagian besar siswa 61,9 % mengalami jerawat ringan. Dan pada kecemasan ringan 64,3%, sedang 19,0% dan berat 16,7%. Sebagian besar kecemasan mereka berada pada tingkat kecemasan ringan 64,3%. Dan menggunakan uji Chi-Square di dapat p-value sebesar 0,000(Î± 0,05). Kesimpulan ada hubungan positif yang sangat signifikan antara hubungan timbulnya acne vulgaris dengan tingkat kecemasan pada Remaja di SMP N1 Likupang Timur. Kata kunci : Acne Vulgaris, Tingkat kecemasan